The Gengnianchun recipe attenuates insulin resistance-induced diminished ovarian reserve through inhibiting the senescence of granulosa cells - Gao, Hongna; Gao, Lingyun; Rao, Yanqiu; Qian, Laidi; Li, Mingqing; Wang, Wenjun (Frontiers in Endocrinology, 2023)
Introduction Insulin resistance (IR) is found in patients with polycystic ovary syndrome (PCOS), but the effects and mechanisms of IR on diminished ovarian reserve (DOR) remain unclear. This study set out to investigate the effects of IR on ovarian reserve; to explore the effects of high concentrations of insulin on the function of ovarian cells in vitro; and to validate the hypothesis that the Gengnianchun recipe (GNC) helps to attenuate DOR caused by IR through reducing the senescence of granulosa cells. Methods Estrus cycle, follicle count, and sex hormone levels were detected to evaluate ovarian function in mice with IR caused by feeding a high-fat diet (HFD). In addition, KGN cells (human granulosa cell line) were treated with high concentrations of insulin. The staining for senescence-associatedβ-galactosidase (SA-β-gal), cell cycle, and expression levels of mRNA and gene proteins related to cell aging were detected in KGN cells treated with high concentrations of insulin. Mice treated with an HFD were fed metformin, GNC, or saline solution for 6 weeks by oral gavage. HOMA-IR, the area under the curve (AUC) of the oral glucose tolerance test (OGTT), levels of fasting blood glucose (FBG), and fasting serum insulin (FINS) were examined to confirm the IR status. Then estrus cycle, follicle count, and sex hormone levels were detected to evaluate ovarian function. Expression levels of mRNA and gene proteins related to cell aging were detected in the ovarian tissue of mice in each group. Results The results demonstrated that IR reduced murine ovarian reserves, and high doses of insulin caused granulosa cells to senesce. There was a considerable improvement in HFD-induced IR status in the metformin (Met) and GNC treatment groups. In addition, the expression levels of aging-associated biomarkers were much lower in GNC mice than Met mice; and both the latter groups had considerably lower levels than the HFD group. Moreover, higher follicle counts in different stages and shorter diestrus in the Met or GNC groups compared to the HFD group indicated that ovarian aging could be largely reversed. Discussion This work showed that: IR impaired ovarian reserve; high concentrations of insulin induced granulosa cell aging; and GNC attenuated ovarian function through inhibiting IR-induced cell aging.